PENGARUH PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DAN KREATIVITAS PESERTA DIDIK TERHADAP HASIL BELAJAR IPA KELAS V DI SDN 147 KOTA JAMBI - Lina Herlina (Jurnal Pesona Dasar, 2019)
Learning approach is the first step toward the learning process that based, inspires and becomes a background of learning methods with specitif theoretical scope. CTL is learning that related daily life context to find new insight. The end of this research is to know the result of the e examination result in Primary School. The sampling use non probability sampling technic. It was based on researched subjective asessment toward students characteristic. The data collection used test and non test technic (quesioner). This researdh is quasi experimental research. The subject war the students of V grade of SDN 147/IV Jambi City consisting of experimental class 5A and controll class 5B, the number of participants is 61 students. The research  result showed: 1) CTL  approach give  more significant effect than expository methode approch towards the learning result, 2) the students with higher creativity have higher learning result than students with low creativity, 3) the students with higher creativity using CTL approach have higher natural science learning research than students with high creativity using expository learning menthode, 4) learner who have low creativity are taught to approach CTL higher learning results of students who are teaching method in ekspository, 5) there is no significant interarctive effects betwen CTL approach and expositoty methode and teh creativity of natural science learning result. Based on the result: it is highly reconed that teachers, expecially natural science teachers in Primary School to apply CTL approach in their learning process and give space for the development of student creativity.